Illuminated poetics: Zen thought in Jorge Eduardo Eielson's poetic writings - Morillo Sotomayor, Alex (2013)
The central motivation of this article is the recognition of the Buddhist thought zen as one of the cultural sources that influenced decisively in the poetic writings of Jorge Eduardo Eielson. In that sense, it first explores the encounter of the poet with this oriental thought, and then the zen principles materialized in his texts. All of this seeks to provide groundsfor the essentialist and totalizing nature of one of the most multifaceted and representative contemporary poetics of the 20th century.